Lots Quality Coverage Survey Technique for Assessment of Determinants of Immunization Coverage in Urban Slum of Mumbai - Kalpak S Kadarkar; Gajanan D Velhal (Medsci Publications, 2016)
Context: Universal immunization of children is crucial and cost-effective public health intervention to reduce morbidity and mortality. Evaluation of immunization coverage provides evidence whether substantial progress towards achieving immunization targets is being made. Aims: The study aimed to assess immunization coverage in urban slum area, reasons for incomplete immunization and impact of socio-demographic profile on the immunization status. Methods and Material: A cross-sectional, descriptive epidemiological study was carried out in urban slum during January 2013 to December 2013. Total 336 children between age of 12-23 months were selected from 21 Lots by using lots quality survey technique. Data was analysed using suitable statistical tests. Results: The overall coverage of immunization in urban slum area was 75.0% (fully immunized), 22.3% (partially immunized) and 2.7% (unimmunized). Reasons for delayed, partial and non-immunization were categorized as lack of information (21.13%), lack of motivation (13.40%) and Obstacles(65.46%). Immunization status was statistically significantly associated with socio-economic status, birth order, place of birth, presence of immunization card, mother's literacy. Conclusions: Completeness of Immunization was significantly correlated with knowledge of mothers on immunization and adequate attention should be given to this if high coverage levels are to be sustained.